Impact of Variable Viscosity on Heat Transfer in a Horizontal Channel With Uniform Transverse Magnetic Field and Non-Uniform Wall Temperature - Jilani, Syed Abdul Khadar; Balamurugan, K. S.; Prasad, J. L. Rama (Communications in Mathematics and Applications, 2025)
This study reconnoiters variable viscosity fluid flow through horizontal channel with parallel walls imperiled to non-uniform temperature and uniform transverse magnetic field. The governing equations have been solved analytically by perturbation process for velocity and temperature fields. The volume flow rate athwart channel, skin friction, Nusselt number at lower and upper plates are calculated and epitomized the impacts of significant parameters through tables. The verdicts show that velocity, temperature are enhanced by increasing viscosity variation parameter.